The Challenge of Rural Developments in the EU Accession Countries : Third World Bank/FAO EU Accession Workshop, Sofia, Bulgaria, June 17-20, 2000 - Csaki, Csaba; Lerman, Zvi (Washington, DC: World Bank, 2013)
This report examines the reforms and policy changes necessary in the rural section of the ten countries that have started the accession process for eventual membership in the European Union (Bulgaria, Czech Republic, Estonia, Hungary, Latvia, Lithuania, Poland, Romania, Slovakia, and Slovenia). The papers in this report are selected from the presentations at the Third World Bank/FAO EU Accession Workshop held in Sofia, Bulgaria, on June 17-20, 2000, and are organized around four topics: 1) Defining the concepts of rural development-options for EU accession candidate countries; 2) Rural development in the European Union; 3) Rural development in Central and Eastern Europe; and 4) International experiences and the role of international organizations in supporting rural development in the EU accession countries.